Educational Structures and Social Closure: Private Schooling, Curriculum Differentiation and Social Segregation in French Secondary Education - Maire, Quentin; Molina, Andres (International Journal of Education Policy and Leadership, 2025)
The relationship between private schooling and social and academic segregation varies around the world. French private schools enroll a minority of secondary students, yet social inequalities are marked in French education. This article argues that the social role of private schooling must be understood in the context of the entire panoply of resources and institutional means of managing socio-academic competition. Specifically, we explore the relationship between curriculum provision and private schooling in producing school segregation in France. Drawing on census data for all secondary education students in major cities, we compare levels of school segregation in middle school, where the curriculum is broadly comprehensive, and in high school, where it is divided. The findings show that private schooling and curriculum both contribute to social segregation.